Fashion and art - Geczy, Adam; Karaminas, Vicki (Berg, 2012)
For at least two centuries, fashion and art have maintained a competitive love-hate relationship. Both fashion and art construct imaginary worlds, and use a language of style to invigorate beliefs, perceptions and ideas. Until now the crossovers of fashion and art have received only scattered treatment and suffered from a dearth of theorization. As an attempt to theorize the area, this collection of new and updated essays is the most well-rounded and authoritative to date. Some of the world's foremost scholars in the field are assembled here to explore the art-fashion nexus in numerous ways: f.